Scale-up challenges and requirement of technology-transfer for cyanobacterial poly (3-hydroxybutyrate) production in industrial scale. Issue 1 (2nd January 2019) - Kamravamanesh, Donya; Kiesenhofer, Daniel; Fluch, Silvia; Lackner, Maximilian; Herwig, Christoph
ABSTRACT: Even though extensive research has been directed toward optimization of the strain, media, and the process, yet there is limited knowledge on the performance and viability of large-scale PHB production lines exploiting cyanobacteria. In this study, the scale-up challenges associated with photosynthetic PHB production are listed. The high PHB producing cyanobacterial mutant, MT_a24, a randomly mutated strain of Synechocystis sp. PCC 6714, has been tested in pilot-scale trials for photosynthetic PHB production under non-sterile conditions. The MT_a24 obtained PHB content of 0.356 g L −1 and 1.7 g L −1 of glycogen from CO2 after 10 days of cultivation using a self-limiting media and non-optimized cultivation parameters. The results obtained here suggest that in order to achieve high PHB productivity values of the lab and to overcome the existing scalability issues reassessment of the optimized parameters needs to be performed during the pilot-scale trials.